Digital interaction and active aging: the impact of social media use on physical activity behavior mediated by social capital and self-efficacy - Liu, Jian; Wang, Chaoxin; Meng, Zhanpeng; Yu, Chuanwen (Frontiers in Psychology, 2025)
BackgroundSocial media use has been linked to higher physical activity levels in older adults, but the mechanisms underlying this connection are not yet well understood. Emerging evidence suggests that social capital may act as a mediator, though little research has explored whether specific dimensions of social capital and self-efficacy mediate this relationship.ObjectiveThis study investigates how social media usage influences older adults’ physical activity behavior, focusing on the mediating roles of social capital—structural, bonding, and bridging—and self-efficacy. The goal is to provide a foundation for strategies to promote physical activity in this population.MethodsA cross-sectional survey was conducted between December 2023 and April 2024 involving 519 social media users (275 male and 244 female). Data were gathered using validated scales for social media usage intensity, physical activity levels (PARS-3), social capital, and self-efficacy. Structural equation modeling (SEM) was applied to examine the relationships between these variables and the mediating effects at play.ResultsOlder adults who engaged more actively with social media exhibited higher physical activity behavior (β = 0.179, p < 0.05). Social capital, across its three dimensions—structural (β = 0.254), bonding (β = 0.294), and bridging (β = 0.237)—significantly mediated the link between social media usage and physical activity (all p < 0.05). Additionally, self-efficacy was a critical, independent mediator (β = 0.242, p < 0.05). A chain-mediating effect involving social capital dimensions and self-efficacy further strengthened this relationship (p < 0.05).ConclusionSocial media use fosters physical activity in older adults by building social capital, mainly structural, bonding, and bridging types, and boosting self-efficacy. Enhancing the social media environment, developing social capital, and supporting self-efficacy are vital strategies for promoting physical activity in this group. The cross-sectional design of this study is a limitation, and future longitudinal research is needed to understand the causal relationships better.